Imatinib Dose Interruption in GIST: High Progression Risk for 3-Year Responders - Helwick, Caroline (MD Conference Express, 2007)
This article discusses multiple clinical trials using imatinib for the treatment of gastrointestinal stromal tumor (GIST). Specific topics include the risk associated with the interruption of imatinib therapy among advanced GIST patients, the link between higher doese of imatinib for GIST and longer progression-free survival, as well as the use of imatinib for recurrence-free survival in completely resected GIST.